Tindak Pidana Kekerasan Dalam Rumah Tangga Menurut Kajian Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Lesnussa, Misye Herlin; Supusepa, Reimon; Latumaerissa, Denny (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The Domestic Violence is a violence that can categorized as frequent acts. The society thought a domestic violence is not a crime.Purposes of the Research: To analyze and examine the forms of dealing with domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence.Methods of the Research: The research method in this writing is normative in the form of library materials, library materials are an in-depth basis (science) of research classified as secondary data, namely using legal materials. The legal materials referred to in the research used are in the form of personal letters, books, official documents, scientific literature and statutory regulations.Results of the Research: The results of the study show that law enforcement of physical violence in the household according to Law No. 23 of 2004 concerning the elimination of domestic violence is an effort to protect every act against someone within the scope of the household, but the reality in the field is that domestic violence is still happening, especially violence. physical for women and children.